Foreign Language Enjoyment, Self-Efficacy, and Willingness to Communicate: Evidence from Arabic Language Education Students - Muhamad Fahri; Muhammad Rizal Mahfuzo; Ahmad Badry (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Developing learners’ communicative proficiency in Arabic requires not only linguistic competence but also a strong psychological disposition, particularly the willingness to communicate (WTC). Previous studies have highlighted the roles of foreign language enjoyment (FLE) and self-efficacy (SE) in fostering WTC, yet empirical evidence in the context of Arabic language learning remains scarce. This study aims to examine the structural relationships among FLE, SE, and WTC among undergraduate students of Arabic Language Education. A quantitative design was adopted using path analysis through the SmartPLS application. Data were collected from 101 participants using three validated instruments: the Short Form of the FLE Scale, the Generalized Self-Efficacy Scale, and the Arabic WTC Scale. The findings reveal that FLE exerts a significant positive effect on SE (β = 0.52, p < .01). However, SE does not significantly predict WTC (β = 0.11, p > .05), indicating that learners’ confidence alone does not guarantee communicative willingness. These results suggest that WTC is influenced by additional factors such as communicative contexts, classroom dynamics, and affective barriers. The study underscores the need for pedagogical interventions that integrate emotional engagement and contextualized communicative practices to strengthen Arabic learners’ WTC.